Cellular uptake mediated by epidermal growth factor receptor facilitates the intracellular activity of phosphorothioate-modified antisense oligonucleotides. Issue 7 (5th March 2018) - Wang, Shiyu; Allen, Nickolas; Vickers, Timothy A; Revenko, Alexey S; Sun, Hong; Liang, Xue-hai; Crooke, Stanley T
Abstract: Chemically modified antisense oligonucleotides (ASOs) with phosphorothioate (PS) linkages have been extensively studied as research and therapeutic agents. PS-ASOs can enter the cell and trigger cleavage of complementary RNA by RNase H1 even in the absence of transfection reagent. A number of cell surface proteins have been identified that bind PS-ASOs and mediate their cellular uptake; however, the mechanisms that lead to productive internalization of PS-ASOs are not well understood. Here, we characterized the interaction between PS-ASOs and epidermal growth factor receptor (EGFR). We found that PS-ASOs trafficked together with EGF and EGFR into clathrin-coated pit structures. Their co-localization was also observed at early endosomes and inside enlarged late endosomes. Reduction of EGFR decreased PS-ASO activity without affecting EGF-mediated signaling pathways and overexpression of EGFR increased PS-ASO activity in cells. Furthermore, reduction of EGFR delays PS-ASO trafficking from early to late endosomes. Thus, EGFR binds to PS-ASOs at the cell surface and mediates essential steps for active (productive) cellular uptake of PS-ASOs through its cargo-dependent trafficking processes which migrate PS-ASOs from early to late endosomes. This EGFR-mediated process can also serve as an additional model to better understand the mechanism of intracellular uptake and endosomal release of PS-ASOs.